Formal and semantic effects of morphological families on word recognition in Hebrew. Issue 1 (2nd January 2019) - Deutsch, Avital; Kuperman, Victor
ABSTRACT: In Hebrew, content words are usually composed of two interleaving morphemes; roots which carry semantic information, and word-patterns which mainly carry grammatical information. The family size effect in languages with non-concatenative morphology has been previously examined only with respect to the root. The present study reports a lexical-decision experiment with 260 Hebrew nouns representing a variety of nominal word-patterns and roots. We observed independent facilitatory effects of morphological family sizes of the roots and the nominal word-patterns. The family size effect of the nominal word-pattern was stronger for words with low frequency. The novelty of these findings is in showing in a within-stimuli design that both morphemes have a role in defining the complex family effect in a language with non-concatenated morphology, despite the massive differences in their linguistic characteristics. The data provide evidence in favour of the proposed multi-dimensional structure of the Hebrew lexicon.